2020
DOI: 10.1002/bdm.2202
|View full text |Cite
|
Sign up to set email alerts
|

The influence of decision time on sensitivity for consequences, moral norms, and preferences for inaction: Time, moral judgments, and the CNI model

Abstract: It is often discussed that moral judgments are either consistent with the principle of utilitarianism or with the principle of deontology. Utilitarianism is a moral principle stating that the right act is the one that produces the best overall outcome. Deontology represents an ethical position indicating that the morality of an action depends on the intrinsic nature of the action regardless of the consequences. Criticism on the structure of moral dilemmas includes the problem that these dilemmas confound norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…12. Different from the effect of cognitive load in Gawronski et al's (2017) studies, Kroneisen and Steghaus (2021) found that time pressure reduced sensitivity to consequences on the CNI model's C parameter. However, this effect failed to replicate in a follow-up study reported in the same article.…”
Section: Notescontrasting
confidence: 69%
“…12. Different from the effect of cognitive load in Gawronski et al's (2017) studies, Kroneisen and Steghaus (2021) found that time pressure reduced sensitivity to consequences on the CNI model's C parameter. However, this effect failed to replicate in a follow-up study reported in the same article.…”
Section: Notescontrasting
confidence: 69%
“…Further analyses using the CNI model suggest that this negative relation is driven by a positive association between need for cognition and sensitivity to moral norms. A conceptually similar link has been found in studies that have used reaction times as an indicator of cognitive elaboration, showing that longer reaction times are associated with greater sensitivity to moral norms (Kroneisen & Steghaus, 2021). A potential explanation for the conflicting findings is that low plausibility of the dilemmas in prior research produces artificial associations that do not reflect genuine differences in moral preferences (see Körner et al, 2019).…”
Section: Need For Cognitionmentioning
confidence: 63%
“…Hierarchical multinomial modelling is an increasingly popular approach in memory research (Marevic et al, 2018;Schaper et al, 2019) but is also used in other research fields (Kroneisen et al, 2021;Kroneisen & Heck, 2020). In line with Schaper et al (2019), we used a twostep strategy to test (1) whether source memory and guessing processes differed between trustworthy and untrustworthy looking cheaters and cooperators and (2) whether there is a relationship between these source-monitoring processes and decision making during the decision-task.…”
Section: Resultsmentioning
confidence: 99%